Some Basic Thesis of Socialism - Lenin on The State and The Applica in Vietnam - Thai, Pham Hong (VNU Journal of Science: Legal Studies; Vol 36 No 2DO - 10.25073/2588-1167/vnuls.4279, 2020)
The essay focuses on explaining the basic issues of Marxism - Leninism about: the nature of the state, the dictatorship of the proletariat, the socialist state, the viewpoint of organizing the exercise of power State and application into Vietnamese conditions through historical periods through analysis of Constitutional provisions and practices. Keywords: marxism - Leninism, state nature, dictatorship of the proletariat, organization of state power, manipulation, constitution, practice. References: C.Mác và Ph.Ăngghen: Toàn tập, t.21, Nxb Chính trị quốc gia, Hà Nội, 1995, tr, 255. [2] V.I. Lê nin, Toàn tập, tập 33, Nxb. Tiến bộ, Matxcơva,1976,tr.110. [3] C.Mác và Ph.Ăngghen:Toàn tập, t.1, Nxb Chính trị quốc gia, Hà Nội, 2002, tr.585. [4] V.I. Lê-nin: Toàn tập, t,33, Nxb Tiến bộ, Mát-xcơ-va, 1981, tr 303 [5] V.I.Lê-nin:Sđd,t37,tr.122 [6] V.I. Lê nin, Toàn tập, t, 39, Nxb, Tiến bộ, Matxcơva,1977,tr.76 . [7] V.I. Lê-nin: Toàn tập, t,34, Nxb Tiến bộ, Mát- xcơ- va, 1976, tr 52 [8] V.I. Lê-nin: Toàn tập, t,21, Nxb Tiến bộ, Mát- xcơ- va, 1980, tr 150 [9] C.Mác và Ph.Ăngghen: Toàn tập, t.20, Nxb Chính trị quốc gia - Sự Thật, Hà Nội, 1994, tr.253. [10] V.I.Lênin: Toàn tập, Nxb Chính trị quốc gia, Hà Nội, 2006, t,35, tr.384. [11] V.I. Lênin: Toàn tập, Nxb Tiến bộ, Mát-xcơ-va, 1976, t 33, tr 101-102,tr. 28, tr.111 [12] V.I. Lê-nin: Toàn tập, Nxb Tiến bộ, Mát-xcơ-va, 1981, t 31, tr 356, tr.356. [13] V.I. Lê-nin: Toàn tập, Nxb Tiến bộ, Mát-xcơ-va, 1978, t 43, tr 380 [14] V.I. Lê-nin: Toàn tập, Nxb Tiến bộ, Mát-xcơ-va, 1981, t 31, tr 356. [15] V.I. Lê-nin: Toàn tập, Nxb Tiến bộ, Mát-xcơ-va, 1978, t 33, tr 109. [16] C. Mác - Ph.Angghen. Tuyển tập. T.1. NXB. Sự thật. H. 1980. tr. 315;tr. 407; tr. 405. [17] Mác- Ph. ănggen Tuyển tập. NXB. Sự thật. H. 1970.tr. 627. [18] V. I. Lênin. Toàn tập. T. 38. NXB. TB. M. 1978. tr. 59.